A REGRESSION MODEL FOR POSITIVE DATA BASED ON THE SLASHED HALF-NORMAL DISTRIBUTION - Gomez, Yolanda M; Gallardo, Diego I; De Castro, Mario (Revstat, 2021)
* In this paper, we discuss several aspects about the slashed half-normal distribution. We reparameter-ize the model based on the mean and we perform comparisons with well-known regression models for positive data. Maximum likelihood estimation of the parameters is carried out through the expectation-maximization algorithm. Some properties of the estimators and two kinds of residuals are assessed in a simulation study. Two real datasets illustrated the proposed model as well as other three models for the sake of comparison. Keywords: * EM algorithm; gamma distribution; half-normal distribution; slashed distribution. AMS Subject Classification: * 62F86, 60E05.